2017
DOI: 10.1111/jsr.12505
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and falls: a systemic review and meta‐analysis of observational studies

Abstract: SUMMARYSeveral epidemiological studies have linked sleep duration with falls; however, the findings yielded inconsistent results. No quantitative analysis has specifically assessed the influence of sleep duration on falls. PubMed and Embase were screened for observational studies from inception to 13 September 2016. A generic inverse-variance method was used to pool the outcome data for sleep duration categories of the lowest category versus reference, and the highest category versus reference with a randomeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 35 publications
1
27
0
2
Order By: Relevance
“…Participants sleeping ~8 h had the lowest prevalence of poor sleep and unfavorable behaviors and characteristics [92]. Interestingly, the U-shaped association was found between sleep duration and serum lipid profiles in Chinese women [93], between sleep duration and diabetic retinopathy [94], and sleep duration and the risk of falls [95].…”
Section: Sleep and Fruit And Vegetable Consumptionmentioning
confidence: 99%
“…Participants sleeping ~8 h had the lowest prevalence of poor sleep and unfavorable behaviors and characteristics [92]. Interestingly, the U-shaped association was found between sleep duration and serum lipid profiles in Chinese women [93], between sleep duration and diabetic retinopathy [94], and sleep duration and the risk of falls [95].…”
Section: Sleep and Fruit And Vegetable Consumptionmentioning
confidence: 99%
“…Since both short as well as long sleep durations appear to be significantly associated with falls [33], it is recommended that older adults be carefully questioned by their care providers about their normal average nights length of sleep, and as required, help them to understand that both too little as well as too much sleep can prove equally problematic in increasing falls and fracture risk. The number of days in the week where poor sleep is evident should also be examined, as the falls risk increases with number of sleep related days reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several papers in this issue focus upon the ageing process and its relationship to sleep. Highly interesting is the systematic review and meta‐analysis by Wu and Sun (), which showed that there was a ‘U‐shaped’ correlation between sleep duration and nocturnal falls. The lowest risk of falls occurred with 7–8 h of sleep.…”
Section: Ageingmentioning
confidence: 99%